Early nutrition in combination with polymorphisms in fatty acid desaturase gene cluster modulate fatty acid composition of cheek cells' glycerophospholipids in school-age children. (September 2019) - Martínez-Zaldívar, Cristina; Azaryah, Hatim; García-Santos, José A.; Demmelmair, Hans; Altmäe, Signe; Reischl, Eva; Rzehak, Peter; Koletzko, Berthold; Campoy, Cristina
Abstract: Variants in the human genes of fatty acid (FA) desaturase 1 ( FADS1 ), 2 ( FADS2 ) and 3 ( FADS 3) are associated with PUFA blood levels. We explored if maternal prenatal supplementation and children's genetic variation in seventeen SNP of the FADS1, FADS2 and FADS3 gene cluster influence twenty-one of the most relevant cheek cells' derived FA in glycerophospholipids (GPL-FA). The study was conducted in 147 Spanish and German mother–children pairs participating in the Nutraceuticals for a Healthier Life (NUHEAL) study at 8, 9 and 9·5 years. Linear and mixed model longitudinal regression analyses were performed. Maternal fish-oil (FO) or FO+5-methyltetrahydrofolate (5-MTHF) supplementation during pregnancy was associated with a significant decrease of arachidonic acid (AA) concentrations in cheek cell GPL in the offspring, from 8 to 9·5 years; furthermore, maternal FO+5-MTHF supplementation was associated with higher n -6 docosapentaenoic acid concentrations in their children at age 8 years. FADS1 rs174556 polymorphism and different FADS2 genotypes were associated with higher concentrations of linoleic and α -linolenic acids in children; moreover, some FADS2 genotypes determined lower AA concentrations in children's cheek cells. It is suggested an interaction between type of prenatal supplementation and the offspring genetic background driving GPL-FA levels at school age. Prenatal FO supplementation, and/or with 5-MTHF, seems to stimulate n -3 and n -6 FA desaturation in the offspring, increasing long-chain PUFA concentrations at school age, but depending on children's FADS1 and FADS2 genotypes. These findings suggest potential early nutrition programming of FA metabolic pathways, but interacting with children's FADS polymorphisms.